The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/w13172387
|View full text |Cite
|
Sign up to set email alerts
|

Anomaly Detection in Dam Behaviour with Machine Learning Classification Models

Abstract: Dam safety assessment is typically made by comparison between the outcome of some predictive model and measured monitoring data. This is done separately for each response variable, and the results are later interpreted before decision making. In this work, three approaches based on machine learning classifiers are evaluated for the joint analysis of a set of monitoring variables: multi-class, two-class and one-class classification. Support vector machines are applied to all prediction tasks, and random forest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
0
12
0
1
Order By: Relevance
“…Overall error analysis represented the cross-validation results of all measuring points in each measurement by calculating the mean absolute error (MAE). It analyzed the error sequence of each measurement as a whole, as seen in Equation (9). The lower the MAE, the higher the overall accuracy.…”
Section: Discussion On the Threshold Of Covariate Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall error analysis represented the cross-validation results of all measuring points in each measurement by calculating the mean absolute error (MAE). It analyzed the error sequence of each measurement as a whole, as seen in Equation (9). The lower the MAE, the higher the overall accuracy.…”
Section: Discussion On the Threshold Of Covariate Introductionmentioning
confidence: 99%
“…At present, the repair of safety monitoring data mainly starts from the dimension of time and mostly adopts linear regression analysis [6,7], principal component analysis [8], machine learning algorithm [9,10], and so on. Among them, Vazifehdan et al [11] proposed a method of combining a naive Bayesian network with tensor decomposition to repair missing data.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some scholars have studied the anomaly identification of uplift pressure during the operation period of concrete dams, and the applicability of various anomaly identification methods is compared [19]. The membership cloud method was proposed for identifying abnormal data by Zhu et al [20], and the uplift pressure monitoring data of the Gongzui gravity dam is identified.…”
Section: Introductionmentioning
confidence: 99%
“…Мониторинг нагрузок на конструкцию и ее реакцию на них может помочь в определении ненормального поведения этой конструкции. В целом мониторинг состоит как из измерений, так и из визуальных осмотров [2]. Для облегчения наблюдения за гидротехническими сооружениями они должны быть постоянно оборудованы соответствующими контрольноизмерительными приборами и/или пунктами наблюдения в соответствии с целями наблюдения, типом и размером сооружения, а также условиями площадки.…”
Section: Introductionunclassified